Efficient energy transfer and luminescence properties of Ca3Y(GaO)3(BO3)4:Tb3+, Eu3+ as a green-to-red colour tunable phosphor under near-UV excitation. Issue 6 (20th January 2017) - Khan, Wasim Ullah; Li, Junhao; Li, Xiaohui; Wu, Qili; Yan, Jing; Xu, Yiqin; Xie, Feiyan; Shi, Jianxin; Wu, Mingmei
Abstract : Energy transfer efficiency can be controlled by adjusting the Tb 3+ /Eu 3+ ratio to realize colour tunable emissions in Ca3 Y(GaO)3 (BO3 )4 . Abstract : A series of Ca3 Y(GaO)3 (BO3 )4 :Tb 3+, Eu 3+ phosphors were prepared by a high-temperature solid-state reaction. Their phase structures were confirmed by powder X-ray diffraction and the element distribution was measured using transmission electron microscopy elemental mapping. The photoluminescence emission and excitation spectra and fluorescence lifetime were studied and discussed in detail. The results revealed that Eu 3+ ions can be efficiently sensitized by Tb 3+ ions under near-UV excitation. In addition, the energy transfer efficiency can be controlled by adjusting the ratio of Eu 3+ and Tb 3+ to realize colour tunable emission from green to red. For Ca3 Y(GaO)3 (BO3 )4 :0.50Tb 3+, 0.10Eu 3+, the emission intensity at 425 K is 78.11% of that at 300 K, being available to near-UV LEDs.